Pangs Of Trauma In Anita: End Of A Beginning And A Life Apart - et. al., Gargi M.M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The word trauma is the Greek term for injury or wound, but nowadays it is an umbrella term for all kinds of wounds, be it physical, emotional or psychological. According to trauma expert Bessel van der Kolk, “Trauma is not the story of something that happened back then,” but “It’s the current imprint of that pain, horror, and fear living inside people.” Also, he notes that trauma is specifically an event that overwhelms the central nervous system, altering the way we process and recall memories. Though trauma is generalised in definitions, trauma and its effect on the victims vary from person to person. This paper explores the notion of trauma and its impact on the central characters of the novels: Anita: End of A Beginning by Renuka Guru and A Life Apart by Neel Mukherjee. The kind of traumatic event, the durability of the trauma and at what age the characters experienced such events are analysed in this paper. Keywords: trauma, abuse, misuse of power, betrayal, fear, guilt. Trauma is ‘an inescapably stressful event that overwhelms people’s existing coping mechanisms’ (qtd. in Spring). A trauma usually happens after a very distressing event, like physical or sexual abuse, natural disaster, wars, betrayal, abuse of power, death of loved ones etc. Its symptoms are mood swings, guilty, nightmares and flashbacks, insomnia, hopelessness, avoidance, depression, anxiety, negative thoughts, inability to formulate, fear, lack of trust etc. It is not necessary that these causes induce trauma in people as it can alter from person to person, that is it is subjective. Cathy Caruth in her book, Unclaimed Experience: Trauma, Narrative, History asserts that in present times, trauma has become universal and bewildering both as an experience and as a subject of study.